1993
DOI: 10.2527/1993.713673x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine somatotropin and dietary lysine influence bone mineralization and mechanical properties of bones in finishing swine2

Abstract: The femur, a rib, and a third metacarpal were collected from 108 barrows (initial weight = 57 kg) and analyzed to determine the effects of porcine somatotropin (pST) and dietary lysine on bone mineralization and mechanical properties. In Exp. 1, pigs were injected daily with 4 mg of pST and fed diets containing 1.0% Ca and .9% P and either .6, .8, 1.0, 1.2, or 1.4% lysine. Control pigs (placebo injection) received the .6% lysine diet. Bone wall thickness (BWT) of the femur increased (linear, P < .05) but ash c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
6
3
Order By: Relevance
“…*Signihcant at P < 0.05 level of probability. (Goodband et al 1993). Our experiment demonstrated similar effects of rpST on the ash content ofvertebrae and ribs (Table 5).…”
Section: Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…*Signihcant at P < 0.05 level of probability. (Goodband et al 1993). Our experiment demonstrated similar effects of rpST on the ash content ofvertebrae and ribs (Table 5).…”
Section: Methodssupporting
confidence: 65%
“…Our experiment demonstrated similar effects of rpST on the ash content ofvertebrae and ribs (Table 5). The reason that the loss of bone ash observed in the present experiment was greater than reported in previous studies (Goodband et al 1993) is unknown. Goodband et al (1993) suggested that an increased cellular requirement for calcium and phosphorus combined with the lower feed intake usualy observed with rpST-treated pigs may explain the lower mineralization of bones of rpST-treated pigs.…”
Section: Methodscontrasting
confidence: 55%
See 3 more Smart Citations